Water and Politics : Clientelism and Reform in Urban Mexico - Herrera, Veronica Maria Sol (Book collections on Project MUSE., 2017)
"Most of the world's population lives in cities in developing countries, where access to basic public services, such as water, electricity, and health clinics, is either inadequate or sorely missing. Through the lens of urban water provision, this book shows how politicians fail to provide reliable and high quality public services because they often benefit politically from manipulating public service provision for electoral gain. In many young democracies, politicians exchange water service for votes or political support, attempting to reward allies or punish political enemies. Surprisingly, the political problem of water provision has become more pronounced in many young democracies, as water service represents a valuable political currency in resource-scarce environments. When do politicians forgo the clientelistic manipulation of water services and invest in programmatic and universal service provision? Water and Politics finds that middle-class and industrial elites play an important role in generating pressure for public service reforms. Based on extensive field research and combining process tracing with a subnational comparative analysis of eight Mexican cities, Water and Politics constructs a framework for understanding the construction of universal service provision in these weak institutional settings"--